Accountability services for verifying compliance in the cloud. (1st January 2012) - Yao, Jinhui; Chen, Shiping; Wang, Chen; Levy, David; Zic, John
The emergence of the cloud has revolutionised the modern day computing. It has provided a cheap and yet reliable outsourcing model for whomever with huge needs for computing resources. And by leveraging service oriented architecture, organisations and companies can wrap their business products as services, to collaborate with others to form business processes. This reinforces the impact of the cloud for that, its enormous computing capacity and network bandwidth make it an ideal platform for collaborative business processes. Within those business processes, each participant is usually an independent entity which may violate the predefined compliance requirements and attempt to avoid the stiff penalty using deceits. Therefore, the mechanism to unarguably verify one's compliance in collaboration is highly critical – the lack of which, will result a chaotic situation where participating entities can act willy-nilly and deny their faults. This paper outlines our approach to enforce strong accountability to address this issue. With accountability, the actions are always linked to the actors with undeniable evidence. We in detail analyse the evidence required to verify different types of compliance and to what extent they can be verified in a provable way. Then we deploy our system with experiment business processes to evaluate its effectiveness.